2021
DOI: 10.1007/s11356-021-17055-8
|View full text |Cite
|
Sign up to set email alerts
|

The outbreak of COVID-19 in Taiwan in late spring 2021: combinations of specific weather conditions and related factors

Abstract: This study aimed to investigate the impact of weather conditions on the daily incidence of the COVID-19 pandemic in late spring 2021 in Taiwan, which is unlike the weather conditions of the COVID-19 outbreak in 2020. Meteorological parameters such as maximum daily temperature, relative humidity, and wind speed were included. The Spearman rank correlation test was used to evaluate the relationship between weather and daily domestic COVID-19 cases. The maximum daily temperature had a positively significant corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
2
7
1
Order By: Relevance
“…Although the prevailing literature generally posits that higher temperatures have a detrimental effect on COVID-19 transmission, leading to fewer confirmed cases [33][34][35], our findings present a different perspective. Our study identified a significant positive correlation between Tmax and confirmed COVID-19 cases across Taiwan, aligning with prior findings [7,8,15,22,36]. Despite evidence that SARS-CoV-2 loses viability at higher temperatures [37], the increase in cases suggests an impactful role of temperature in COVID-19 spread.…”
Section: Meteorological Factors and Covid-19 Incidencesupporting
confidence: 89%
See 3 more Smart Citations
“…Although the prevailing literature generally posits that higher temperatures have a detrimental effect on COVID-19 transmission, leading to fewer confirmed cases [33][34][35], our findings present a different perspective. Our study identified a significant positive correlation between Tmax and confirmed COVID-19 cases across Taiwan, aligning with prior findings [7,8,15,22,36]. Despite evidence that SARS-CoV-2 loses viability at higher temperatures [37], the increase in cases suggests an impactful role of temperature in COVID-19 spread.…”
Section: Meteorological Factors and Covid-19 Incidencesupporting
confidence: 89%
“…• Wind speed (WS): Measured in meters per second (m/s), indicating the speed of wind observed at the stations. WS was found to have a positive correlation with the number of confirmed COVID-19 cases in prior studies [22,25,26].…”
mentioning
confidence: 68%
See 2 more Smart Citations
“… Mofijur M et al [ 75 ] 2020 Bangladesh 1 Ma y 2020 to 31 Ma y 2020 31 Spearman rank correlation 8 Temperature (max, min, ave), wind speed, rainfall, relative humidity Minimum temperature and average The temperature had a significant relationship with new COVID-19 cases. Chang SA et al [ 76 ] 2021 Taiwan May 1–May 28, 2021 28 Spearman rank correlation 6 Maximum temperature, wind speed, relative humidity Maximum daily temperature significantly Positively correlated with daily new COVID-19 cases. Bilal et al [ 77 ] 2021 USA March 2, 2020, to September 17, 2020, 200 Spearman, Kendal rank correlation 7 Maximum temperature, rainfall, relative humidity, daily new cases, daily new deaths of COVID-19 Temperature, humidity, environmental quality index, and rainfall are significant Variables related to the COVID-19 pandemic in the USA's top 10 most affected states.…”
Section: Resultsmentioning
confidence: 99%